Asymmetric Influence of Vocalic Context on Mandarin Sibilants: Evidence From ERP Studies - Meng, Yaxuan; Kotzor, Sandra; Xu, Chenzi; S. Z. Wynne, Hilary; Lahiri, Aditi (Frontiers in Human Neuroscience, 2021)
In the present study, we examine the interactive effect of vowels on Mandarin fricative sibilants using a passive oddball paradigm to determine whether the HEIGHT features of vowels can spread on the surface and influence preceding consonants with unspecified features. The stimuli are two pairs of Mandarin words ([sa] ~ [ʂa] and [su] ~ [ʂu]) contrasting in vowel HEIGHT ([LOW] vs. [HIGH]). Each word in the same pair was presented both as standard and deviant, resulting in four conditions (/standard/[deviant]: /sa/[ʂa] ~ /ʂa/[sa] and /su/[ʂu] ~ /ʂu/[su]). In line with the Featurally Underspecified Lexicon (FUL) model, asymmetric patterns of processing were found in the [su] ~ [ʂu] word pair where both the MMN (mismatch negativity) and LDN (late discriminative negativity) components were more negative in /su/[ʂu] (mismatch) than in /ʂu/[su] (nomismatch), suggesting the spreading of the feature [HIGH] from the vowel [u] to [ʂ] on the surface. In the [sa] ~ [ʂa] pair, however, symmetric negativities (for both MMN and LDN) were observed as there is no conflict between the surface feature [LOW] from [a] to [ʂ] and the underlying specified feature [LOW] of [s]. These results confirm that not all features are fully specified in the mental lexicon. Features of vowels can spread on the surface and influence surrounding unspecified segments.